Aunt dimity and the king's ransom ebook - Atherton, Nancy (Aunt Dimity, 2018)
In the 23rd installment of the bestselling Aunt Dimity series, a dark and stormy night kicks off a ghost chase in rural England On a dull and dreary October day, Lori Shepherd and her husband Bill set off for the historic town of Rye, on the southeast coast of England, for a quiet weekend together without the kids. Bill must first pay a visit to a reclusive client—but after Lori drops him off, a powerful storm drives her off course and leaves her stranded in an ancient, rambling inn called The King's Ransom. When Lori is spooked by ghostly noises in the night, Aunt Dimity reminds her rather tartly that not all ghosts intend to harm the living. But the longer Lori is stuck at the inn, the stranger things seem. She learns that the inn was once a hangout for smugglers, and that it's riddled with secret tunnels the smugglers used to reach a network of hidden caves. Then there's the inn's cook—a brawny, gruff ex-con—who seems to have a beef with a mysterious French guest. Are the noises Lori hears made by the spirits of long dead smugglers? Or should she be more worried by the inn's living inhabitants? Joining forces with her new friend Bishop Wyndham, and guided by Aunt Dimity's wise counsel, Lori sets out to discover once and for all who—or what—is haunting The King's Ransom.